Lessons Learned From Translational Research in Neuromuscular Diseases: Impact on Study Design, Outcome Measures and Managing Expectation - Stimpson, Georgia; Chesshyre, Mary; Baranello, Giovanni; Muntoni, Francesco (Frontiers in Genetics, 2021)
Spinal Muscular Atrophy (SMA) and Duchenne Muscular Dystrophy (DMD), two of the most common, child onset, rare neuromuscular disorders, present a case study for the translation of preclinical research into clinical work. Over the past decade, well-designed clinical trials and innovative methods have led to the approval of several novel therapies for SMA and DMD, with many more in the pipeline. This review discusses several features that must be considered during trial design for neuromuscular diseases, as well as other rare diseases, to maximise the possibility of trial success using historic examples. These features include well-defined inclusion criteria, matching criteria, alternatives to placebo-controlled trials and the selection of trial endpoints. These features will be particularly important in the coming years as the investigation into innovative therapy approaches for neuromuscular diseases continues.